Architecture and solutions of 5G ultra dense network - Jianmin ZHANG; Weiliang XIE; Fengyi YANG (Dianxin kexue)
Ultra dense network（UDN）is referred to as the most efficient technique for meeting the challenges of 1 000 times higher trafficvolume and 10～100 times higher user data rate，which can improve the network capacity dramatically through network densification.However，due to the limited coverage and higher density of small cell，the problems of frequent handover and inter-cell interference become intractable，which degrade the system capacity and user experience.Therefore，in order to satisfy the challenges of coverage and capacity simultaneously，the architecture of 5G ultra dense network was proposed，which was characterized as the separation of control and user planes and cluster-based centralized control.Besides，regarding to the UDN scenarios of macro-micro and micro-micro，different solutions were presented，respectively.In addition，the problems and challenges of the architecture of 5G ultra dense network were also discussed in detail，providing reference for future research and development.